A new and efficient method for producing food ingredients high in l‐ornithine using unused parts of white cabbage (Brassica oleracea var. capitata). Issue 12 (7th September 2022) - Kurata, Koji; Chiyoda, Michiko; Ito, Machi; Furuse, Mitsuhiro
Abstract: A surplus of unused parts of vegetables (e.g., white cabbage [cabbage] cores and outer leaves) is generated daily by factories of fresh‐cut vegetables. These parts are difficult to effectively utilize and are often discarded as biodegradable industrial waste. This study aimed to develop an efficient method for producing l ‐ornithine from cabbage residues. First, we added protease (Sumizyme FP) to the cores and outer leaves of sterile cabbages. After 8 days, the amount of l ‐arginine released was approximately fivefold the amount in the initial content. As l ‐arginine is a precursor of l ‐ornithine, the addition of protease combined with Pediococcus pentosaceus produced l ‐ornithine. However, the rapid lactic acid fermentation suppressed the metabolism of l ‐arginine to l ‐ornithine, which we overcame by adjusting the pH by adding eggshell. The anaerobic fermentation of the cores and outer leaves of sterile cabbages with 5% eggshell for 8 days produced 184 ± 2 μmol of l ‐ornithine/100 g cabbage. Practical applications: This level of l ‐ornithine production is higher than that observed in freshwater clams (81–116 μmol/100 g), which are considered to be high in l ‐ornithine. This method can be applied to the production of inexpensive and safe l ‐ornithine‐containing food materials derived from vegetables. Furthermore, ingestions of vegetables fermented by this method would provide a variety of health benefits of l ‐ornithine. The widespread adoption of this method will not only reduce the amount of waste generated daily from fresh‐cut vegetable factories, but will also enable upcycling as a higher value‐added food material. Abstract : A surplus of unused parts of vegetables (e.g., white cabbage cores and outer leaves) is generated daily by factories of fresh‐cut vegetables. Anaerobic fermentation of these vegetable residues with protease (Sumizyme FP) and Pediococcus pentosaceus did not produced l ‐ornithine, however, when eggshell was added to them, large amounts of l ‐ornithine were stably produced. These fermented products are sustainable food ingredients with the potential health benefits of l ‐ornithine.